A Rhetorical Strategy Of Ethical Appeals In Tgb Muhammad Zainul Majdi’s Moderate Discourse Of Da’wah Nusantara In Bali: - - M. Rifqi Subakti Bahtiar; Hishammudin Salim; Nursyafawati Ahmad Sani; Hamzani Wathoni (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2022)
The goal of this qualitative descriptive study is to understand how TGB Muhammad Zainul Majdi employed the rhetorical device of ethos (ethical appeals) to establish power/credibility and moderate speech. As a result, the researcher chose to focus on one of TGB Muhammad Zainul Majdi's most fascinating talks, specifically one that was given in Bali and attended by people from various socioeconomic classes, educational backgrounds, and even religious backgrounds. This is also a da'wah from the Archipelago TGB Muhammad Zainul Majdi in relation to the opening of the Wikondo pavilion. Discourse analysis is the data analysis technique that is being employed. It consists of three parts: transcription of speech from video sources, coding of language elements, and classification and inference. Based on the results of the document analysis of the transcription of speech using discourse analysis, it was found that TGB Muhammad Zainul Majdi used the similitude approach to conduct ethical appeal and attract listeners. In that case, similitude is widely used by employing the subject pronoun we, both inclusive and also inferential subject pronoun we. Then moderate speech to convey the message wisely and well is born from the delivery of TGB Muhammad Zainul Majdi.